2013
DOI: 10.1111/imre.12038
|View full text |Cite
|
Sign up to set email alerts
|

Why Immigrant Background Matters for University Participation: A Comparison of Switzerland and Canada

Abstract: This article extends our understanding of the difference in university participation between students with and without immigrant backgrounds by contrasting outcomes in Switzerland and Canada and by the use of new longitudinal data that are comparable between the countries. The research includes family socio-demographic characteristics, family aspirations regarding university education, and the student's secondary school performance as explanatory variables of university attendance patterns. In Switzerland, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…For example, based on his review of the evidence, Modood (2004) suggests that what drives the educational success of the British South Asian and Chinese communities is that parents are able to get their children to internalize high educational ambitions and to enforce appropriate behaviour, despite their relatively disadvantaged status in British society. Picot and Hou (2013) find that parental and student aspirations Bexplain^a large share of the positive university attendance gap between various generations of immigrants and students with two Canadian-born parents. They note that immigrants display a significant advantage in university attendance, even among some who performed poorly at secondary school.…”
Section: Literaturementioning
confidence: 87%
“…For example, based on his review of the evidence, Modood (2004) suggests that what drives the educational success of the British South Asian and Chinese communities is that parents are able to get their children to internalize high educational ambitions and to enforce appropriate behaviour, despite their relatively disadvantaged status in British society. Picot and Hou (2013) find that parental and student aspirations Bexplain^a large share of the positive university attendance gap between various generations of immigrants and students with two Canadian-born parents. They note that immigrants display a significant advantage in university attendance, even among some who performed poorly at secondary school.…”
Section: Literaturementioning
confidence: 87%
“…It also allows for cross-national comparative studies with datasets of other countries that have done the same (for examples of comparative analyses, see Picot & Hou, 2013;Murdoch et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, international comparative research could be further developed to study the impact of economic, institutional or social policy as well as other contexts on individual life courses (see, e.g. Buchmann, Kriesi, Koomen, Imdorf & Basler, 2016;Imdorf, Helbling & Inui, forthcoming;Imdorf & Hupka-Brunner, 2015;Kamanzi, Guégnard, Imdorf, Koomen & Murdoch, 2014;Murdoch, Guégnard, Griga, Koomen & Imdorf, 2016;Murdoch et al, 2017;Picot & Hou, 2013). To date, around 270 researchers and students from national and international institutions across a multitude of disciplines have been working with the TREE1 data.…”
Section: Data Usementioning
confidence: 99%
“…It has been found that it is harder for individuals with migrant backgrounds to access higher education. A significant effect of migration status is found in the transition to upper-secondary education (Hupka-Brunner, Sacchi, & Stalder, 2010;Wolter & Zumbuehl, 2017) and in the transition to tertiary education (Picot & Hou, 2013).…”
Section: Sociodemographic Factorsmentioning
confidence: 99%